Muscadine Grape and Wine Polyphenols Alleviated the Severity of Collagen Induced Arthritis in Mice - Christman, Lindsey (Curr Dev Nutr, 2021)
OBJECTIVES: The aim of this study was to investigate the effect of concentrated muscadine grape polyphenols (MGP) and muscadine wine polyphenols (MWP) on the onset and progression of collagen induced arthritis (CIA) in mice. METHODS: MGP and MWP were concentrated using Amberlite XAD16N resin. Polyphenol composition was determined on HPLC. Male DBA/1 mice were divided into four treatment groups as (1) healthy control, (2) CIA control, (3) CIA + MWP, and (4) CIA + MGP. Arthritis was induced by intradermal injection of type II collagen on days 0 and day 21. Mice in groups 3 and 4 were gavaged with MWP and MGP using a dose of 400 mg/kg body weight for a total of 21 days. Severity of CIA was evaluated using clinical arthritic score and inflammation in the hind-paws. Plasma levels of cytokines, proteases, and anti-collagen antibody were measured using ELISA. RESULTS: MGP and MWP contained anthocyanin 3, 5-diglucosides, flavonols, and ellagic acid. Mice in the CIA control group had an onset of arthritis on day 18, which was delayed to day 22 and 24 by MWP and MGP, respectively (P < 0.05). Severity of arthritis was much lower in mice gavaged with muscadine polyphenols after the onset. On day 42, the average arthritic score of mice in the CIA control group progressed to 7.75 on a scale of 0–16, while MGP and MWP significantly reduced this score to 3.75 and 4.00, respectively (P < 0.01). In addition, MGP and MWP significantly reduced the plasma concentration of TNF-α, IL-6, anti-collagen antibodies, and matrix metalloproteinase-3 in CIA mice but not to the same level of healthy mice. The plasma concentration of IL-17 was drastically elevated in CIA mice, but it was not affected by MWP or MGP like other cytokines. This suggested that muscadine polyphenols had limited impact on the Th17 cells in the immune system. Mice gavaged with MPG and MWP had comparable plasma cytokine content, suggesting similar anti-inflammation activity. CONCLUSIONS: Muscadine grape and wine polyphenols blunt the development of arthritis in mice by reducing the levels of key inflammatory cytokines, antibodies, and proteases, and may offer a promising dietary approach to manage arthritic symptoms. FUNDING SOURCES: Florida Department of Agriculture and Consumer Service and Florida Viticulture Advisory Council.